Theoretic and Legal Approaches to the Definition of Religious Extremism - Rakhimbekov, Meiram (Journal of Advanced Research in Law and Economics; Vol 9 No 1 (2018): JARLE Volume IX Issue 1(31) Spring 2018, 2018)
The article deals with issues related to the effective counteraction to religious extremism – one of the most dangerous types of extremism. The author examines the approaches of Kazakh and foreign scientists to the scientific and practical definition of the concept of ‘religious extremism’. Nowadays there is no clear legislative consolidation of the concept of ‘religious extremism’ which does not contribute to the targeted and substantive resistance to this phenomenon and does not provide a unified, consistent law enforcement practice. The author offers obligatory and alternative criteria (signs) allowing to distinguish religious extremism among other types of crime. It is proposed to fix as a form of extremism-the motivation of citizens to refuse to perform civil duties or commit other illegal acts.